2020
DOI: 10.5194/wes-2020-50
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parameterization of Wind Evolution using Lidar

Abstract: Abstract. Wind evolution refers to the change of the turbulence structure of the eddies over time while the eddies are advected by the main flow over space. With the development of the lidar-assisted wind turbine control, modelling of the wind evolution becomes an interesting topic, because the control system should only react to the changes in the wind field which can be predicted accurately over the distance to avoid harmful and unnecessary control action. This paper aims to achieve a parameterization model … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…As shown in Table 5, R 2 of all recommended cases ranges from 0.67 to 0.83. These results are much better than that of the preliminary study (Chen, 2019); in particular, the prediction accuracy of the offset parameter b has been significantly improved. This is mainly owing to the use of the ARD-SE kernel, which can help to select predictors reasonably and give different weights to predictors according to their relevant importance for the prediction, whereas kernel functions with a common length scale for predictors were applied in the preliminary study.…”
Section: Model Evaluationcontrasting
confidence: 61%
See 1 more Smart Citation
“…As shown in Table 5, R 2 of all recommended cases ranges from 0.67 to 0.83. These results are much better than that of the preliminary study (Chen, 2019); in particular, the prediction accuracy of the offset parameter b has been significantly improved. This is mainly owing to the use of the ARD-SE kernel, which can help to select predictors reasonably and give different weights to predictors according to their relevant importance for the prediction, whereas kernel functions with a common length scale for predictors were applied in the preliminary study.…”
Section: Model Evaluationcontrasting
confidence: 61%
“…In addition, it is desired to gain some insights into the complex relationships between wind evolution and wind-field-related variables such as wind statistics, atmospheric stability, and relative positions of measurement points. For these purposes, a previous study (Chen, 2019) was done to explore different supervised machine learning algorithms on a simple level, including stepwise linear regression (see, e.g., Hocking, 1976), regression tree (see, e.g., Breiman et al, 1984), support vector regression (see, e.g., Vapnik, 1995), and Gaussian process regression (see, e.g., Rasmussen and Williams, 2006). It was found that Gaussian process regression, overall, performs the best for prediction of wind evolution model parameters, and thus its potential is further analyzed in this study with more extensive data.…”
Section: Y Chen Et Al: Parameterization Of Wind Evolution Using Lidarmentioning
confidence: 99%
“…(6). A single DWL can be used to study the longitudinal co-coherence (Sjöholm et al, 2010;Davoust and von Terzi, 2016;Cheynet et al, 2017b;Debnath et al, 2020;Chen et al, 2020). Also, the value of the C x as a function of the range gate can provide additional information on the influence of the coastline on the flow characteristics.…”
Section: Co-coherence Estimatesmentioning
confidence: 99%
“…It is worth mention that several authors [5], [8] use formulas of the squared coherence. For conformity with the formula in IEC Kaimal model, we use the non-squared formula here.…”
Section: B Wind Modelmentioning
confidence: 99%
“…Sketch of previous and proposed method on wind preview quality estimation the correlation of measurements at two positions within the rotor plane. In LES simulations [5] and real application [8], the turbulence coherence structure varies with atmospheric conditions, such that the lidar wind preview quality changes as well. Previously, the wind preview studies were done mainly with a frequency-based correlation study by analyzing the coherence between REWS of the turbine to the one provided by the lidar [1], [5], [7].…”
Section: Introductionmentioning
confidence: 99%